Longitudinal Changes in Sexual Functioning as Women Transition Through Menopause: Results from the Study of Women’s Health Across the Nation (SWAN) - Avis, Nancy E. (2009)
OBJECTIVE: Sexual functioning is an important component of women’s lives. The extent to which the menopause transition is associated with decreased sexual functioning remains inconclusive. This study seeks to determine if advancing through the menopause transition is associated with changes in sexual functioning. DESIGN: A prospective, longitudinal cohort study of women aged 42–52 at baseline recruited at 7 US sites (N=3302) in the Study of Women’s Health Across the Nation (SWAN). Cohort eligible women had an intact uterus, at least one ovary, were not currently using exogenous hormones, were either pre- or early perimenopausal, and self-identified as one of the study’s designated racial/ethnic groups. Data from the baseline interview and six annual follow-up visits are reported. Outcomes are self-reported ratings of importance of sex; frequency of sexual desire, arousal, masturbation, sexual intercourse, and pain during intercourse; degree of emotional satisfaction and physical pleasure. RESULTS: Adjusting for baseline age, chronological aging, and relevant social, health, and psychological parameters, the odds of reporting vaginal or pelvic pain increased and desire decreased by late perimenopause. Masturbation increased at early perimenopause, but declined during postmenopause. Menopausal transition was unrelated to other outcomes. Health, psychological functioning, and importance of sex were related to all sexual function outcomes. Age, race/ethnicity, marital status, change in relationship, and vaginal dryness were also associated with sexual functioning. CONCLUSIONS: Pain during sexual intercourse increases and sexual desire decreases over the menopausal transition. Masturbation increases during the early transition, but then declines in postmenopause. Adjusting for other factors, the menopausal transition was not independently associated with reports of the importance of sex, sexual arousal, frequency of sexual intercourse, emotional satisfaction with partner, or physical pleasure.